Study of historical mortars from Villa Romana of Frielas, Portugal - Ahmmed, Tanjil (2022)
The Roman villa of Frielas is an archaeological site from 3rd – 6 th century AD located in Loures, Portugal. The villa is on excavation since 1997. The site is an area of 3500 m2 . The area still under excavation corresponds to the villa's urban pars. The villa has two construction phases, the first phase is very limited with structural evidence and mostly destroyed during the construction of 2nd phase. The 2nd phase has evidence of architectural features with functionality mainly, some compartments surrounding the peristyle with portico and mosaic floor passages. And its abandonment occurred at the beginning of the 7th century A.D. The abandonment phase has no remarkable architectural features, except some unfinished walls or destruction of earlier phases. A total of eighteen mortar samples were collected from the different structures of the villa with different functional uses (render, filler, and floor) and analyzed by a multi-analytical approach by means of Optical Microscopy, (Stereo zoom and Petrographic microscope), X ray Diffraction (XRD), Variable Pressure Scanning Electron Microscopy coupled with Energy Dispersive X-ray Spectroscopy (VP-SEM-EDS), Thermogravimetric analysis (TGA DTG), Acid attack and Granulometric analysis. The results revealed a similar composition of calcitic aerial binder, while differences in aggregates allowed to establish 4 groups. Raw materials are local and within a radius of 5Km. There was no prominent variation that can suggest a different chronology between the four groups. Though, it is assumed that there might be some renovation, restoration, or partial rebuilding that occurred in the same period. In terms of production technology, it is evident that the Vitruvius rules were not followed; R E S U M O: Estudo de argamassas históricas da villa romana de Frielas (Loures, Portugal) A villa romana de Frielas é um sítio arqueológico do século III ao IV DC localizado em Loures, Portugal. A villa romana está em escavação desde 1997. O local tem uma área de 3500 m2 . A área ainda em escavação corresponde à área urbana da villa. Esta apresenta duas fases de construção sendo que a primeira fase é muito limitada com poucas evidências estruturais e/ou destruídas durante a construção da 2ª fase. A 2ª fase apresenta evidências de características arquitetónicas com funcionalidade principalmente, alguns compartimentos circundando o peristilo com passagens de pórtico e piso de mosaico. E seu abandono ocorreu no início do século 7 d.C. A fase de abandono não tem características arquitetônicas notáveis, exceto algumas paredes inacabadas ou destruição de fases anteriores. Um total de dezoito amostras de argamassas com usos funcionais distintos (reboco, enchimento e assentamento) foram recolhidas, em diferentes estruturas da villa, e analisadas por uma abordagem multi-analítica compreendendo a Microscopia Ótica (estereomicroscopia e petrografia), a Difração de raios X (DRX), a Microscopia Eletrónica de Varrimento – Espectroscopia de Energia Dispersiva de raios X (MEV-EDS), a Análise Termogravimétrica (ATG-DTG), o Ataque Ácido e a Análise Granulométrica. Os resultados revelaram que as argamassas estudadas apresentam uma composição semelhante, ligante de cal calcítica, enquanto que as diferenças nos agregados permitiram estabelecer 4 grupos. As matérias-primas são locais e num raio de 5km. Não se verificaram variações significativas que possam sugerir uma cronologia diferente entre os quatro grupos. Porém, presume-se que pode ter havido alguma renovação, restauro ou reconstrução parcial ocorrida no mesmo período. Em termos de tecnologia de produção, é evidente que as regras de Vitruvius não foram seguidas.